2004
DOI: 10.1038/nn1181
|View full text |Cite
|
Sign up to set email alerts
|

Bi-directional effects of GABAB receptor agonists on the mesolimbic dopamine system

Abstract: The rewarding effect of drugs of abuse is mediated by activation of the mesolimbic dopamine system, which is inhibited by putative anti-craving compounds. Interestingly, different GABA(B) receptor agonists can exert similarly opposing effects on the reward pathway, but the cellular mechanisms involved are unknown. Here we found that the coupling efficacy (EC(50)) of G-protein-gated inwardly rectifying potassium (GIRK, Kir3) channels to GABA(B) receptor was much lower in dopamine neurons than in GABA neurons of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
311
1
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 319 publications
(334 citation statements)
references
References 47 publications
19
311
1
3
Order By: Relevance
“…The direct inhibitory influence of GABA B R and D 2 R activation on VTA DA neurons is mediated primarily by activation of G protein-gated inwardly rectifying K + (GIRK/ Kir3) channels found in the somatodendritic compartment (Beckstead et al, 2004;Cruz et al, 2004). Although GIRK1/ GIRK2 heterotetramers are considered to be the prototypical neuronal GIRK channel (Lujan et al, 2014), VTA DA neurons express a GIRK2/GIRK3 heteromer (Cruz et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The direct inhibitory influence of GABA B R and D 2 R activation on VTA DA neurons is mediated primarily by activation of G protein-gated inwardly rectifying K + (GIRK/ Kir3) channels found in the somatodendritic compartment (Beckstead et al, 2004;Cruz et al, 2004). Although GIRK1/ GIRK2 heterotetramers are considered to be the prototypical neuronal GIRK channel (Lujan et al, 2014), VTA DA neurons express a GIRK2/GIRK3 heteromer (Cruz et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Although GIRK1/ GIRK2 heterotetramers are considered to be the prototypical neuronal GIRK channel (Lujan et al, 2014), VTA DA neurons express a GIRK2/GIRK3 heteromer (Cruz et al, 2004). Girk2 ablation eliminates all GIRK channel activity in VTA DA neurons (Beckstead et al, 2004;Cruz et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Baclofen is a gamma-amino butyric acid (GABA) derivative that acts as an agonist at the GABA B receptor inducing presynaptic motor neuron inhibition and a central antispastic response [1]. While baclofen has been used primarily to limit spasticity in spinal cord disorders, it also has been studied as an inhibitor of dopamine reward pathways to treat drug abuse [2]. Baclofen is lipophilic, readily crosses the blood-brain barrier, has an elimination half-life of approximately 2 to 6 hours, and primarily is cleared via renal excretion [1].…”
Section: Clinical Narrativementioning
confidence: 99%
“…It has been postulated that the relative dopaminergic hypofunction produced by DBAs causes overactivity of cholinergic mechanisms [3]. With respect to GABA receptors, rodent models have shown that GABA B receptors are expressed on both dopamine neurons, as well as GABA neurons [2]. In rats exposed to baclofen, it was shown that activation of GABA B receptors inhibited both GABAergic and dopaminergic neurons, and decreased dopamine release [2].…”
Section: Clinical Narrativementioning
confidence: 99%
See 1 more Smart Citation